Leukocytoclastic vasculitis as a cutaneous manifestation of ChAdOx1 nCoV‐19 corona virus vaccine (recombinant). Issue 6 (5th October 2021) - Sandhu, Sunmeet; Bhatnagar, Anuj; Kumar, Harish; Dixit, Prashant Kumar; Paliwal, Gourang; Suhag, Devinder Kumar; Patil, Chetan; Mitra, Debdeep
Abstract: With the present COVID‐19 vaccination drive across the world, adverse skin reactions post COVID‐19 vaccine is expected. Majority of these reactions seen were transient or local injection site reactions. However, as the larger population is being vaccinated, certain uncommon dermatological presentations including leukocytoclastic vasculitis, pityriasis rosea, and exacerbation of pre‐existing autoimmune diseases are now being reported. Among all the COVID‐19 vaccines, most of these reactions are seen with messenger ribonucleic acid‐based Pfizer/BioNTech (BNT162b2) and Moderna (mRNA‐1273) vaccine. We report two cases of leukocytoclastic vasculitis following ChAdOx1 nCoV‐19 corona virus vaccine (recombinant) that bring out potential new dermatological manifestations of recombinant corona virus vaccine being administered across the European, South American, and Asian countries. It is important for all health care workers and patients to be aware of the corona virus vaccine associated adverse cutaneous reactions.